Application of Role-Playing Model in Physical Education to Develop Student Social Skills - B Budiman; Adang Suherman; Beltasar Tarigan; Tite Juliantine; Erick Burhaein (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Social skill is one of the life skills that must be possessed by students. Students who have good social skills can interact with their peers and show a positive attitude in both school and social settings. Role-playing learning model is considered as a model that can develop social skills. However, there is no empirical evidence that role-playing learning model in physical education can develop student social skills. Therefore, this study was aimed to examine the effect of role-playing model in physical education on student social skills. This study used an experimental method with One Group Pre-Test Post-Test Design. This study involved 30 sixth grade students of public elementary schools in one of school in West Java. The instrument used was a social skill questionnaire compiled by the researcher. The test used to test the hypothesis of this study was the paired sample t-test using SPSS version 25 with a signification level of α=0.05. The results of this study showed that there was an effect of role-playing model on student social skills. This study concludes that the use of role-playing model in physical education has a positive impact on student social skills. This model is able to play a strategic role as an educational tool, especially for teaching social skills.